Equitable education for migrant students? Investigating the educational success of newly arrived migrants in Flanders - Seynhaeve, Shauny; Vanbuel, Marieke; Kavadias, Dimokritos; Deygers, Bart (Frontiers in Education, 2024)
Introduction Previous research has uncovered various inequalities for immigrant students in education systems worldwide. Yet, the degree to which diverse background factors, such as socio-economic status and prior educational trajectory, contribute to these educational disadvantages remains uncertain. Methods Using data from the Flemish administrative database (2009–2019) on 48,340 mainstream students and 1,022 Newly Arrived Migrant Students (NAMS) across 685 schools, this study examines NAMS' passing and dropout rates in Flemish secondary education in comparison to the outcomes of their peers without a recent migration background. Data included demographic background variables, school variables, and indicators of educational outcomes. Results A cross-classified multilevel regression analysis showed that, after controlling for background variables, NAMS still show higher probabilities of failing a year and of dropping out. Moreover, the impact of SES is stronger for native students than for NAMS. Discussion These results suggest the existence of a migrant background effect disadvantaging NAMS in Flemish secondary education.